Using an ICU Diary to Communicate With Family Members of COVID-19 Patients in ICU: A Case Report. (27th July 2021) - Haruna, Junpei; Tatsumi, Hiroomi; Kazuma, Satoshi; Kuroda, Hiromitsu; Goto, Yuya; Aisaka, Wakiko; Terada, Hirofumi; Masuda, Yoshiki
Visitation restrictions for family members are problematic in intensive care management due to the COVID-19 pandemic. We analyzed the usefulness of an intensive care unit (ICU) diary about the experiences of family members of critical COVID-19 patients. Four family members of 2 COVID-19 patients participated in this report. Both patients were transferred to our ICU after 2 weeks of treatment at another ICU. An ICU diary was given to their family members post-transfer. The family members were interviewed before and after the patients' discharge; the recorded interviews were analyzed and categorized into several clusters using a text mining method. Five categories regarding their anxious feelings were classified before the use of the ICU diary, and 3 categories were based on their positive feelings after the use of the ICU diary. Intensive care unit diaries may be beneficial for disclosing patients' information when visitation restrictions are exercised due to the COVID-19 pandemic.